Revisiting Integrated Mobile Advertising Model in Indonesia: A Replication Study - Pradipta, Naufal; Santoso, Adhi S; Nelloh, Liza Agustina M (UI Scholars Hub, 2022)
Manuscript type: Research Article Research Aims: Kim's previous study proposed a web advertising model such as personalization and flow theory toward purchase intention and its antecedents. The current research will re-assess the model in Indonesia. Design/methodology/approach: Using Structural Equation Modelling (SEM) toward 211 respondents Research Findings: This study showed that credibility is insignificant to advertising value and flow experience, and entertainment and incentives are insignificant to flow experience. Thus, informativeness is insignificant to advertising value and flow experience. Hence irritation is also insignificant to advertising value and flow experience. However, personalization showed a significant effect on flow experience but insignificant toward advertising value. Theoretical Contribution/Originality: Insignificant effect of the web advertising model, such as personalization and flow theory toward purchase intention and its antecedents Practitioner/Policy Implication: The promotion process on smartphone media to implement the web advertising model.